Pemberdayaan Potensi Ekonomi Produktif Masyarakat Berbasis Potensi Desa Melalui Penguatan Lembaga Keuangan Mikro dan Forum Pemberdayaan KeluargaDi Desa Sumberejo Kecamatan Ambulu Kabupaten Jember - Hary Sulaksono; Tamriatin Hidayah; Gatot Sugeng Purwono (STIE Mandala Jember, 2015)
The key issue is KKN-PPM Increased self-financing and self empowerment communities. The purpose of this activity, are: 1. General purpose referring to guide implementation of the Higher Education KKN PPM Kemendikbud, while specific objectives include: a) Increase awareness and empathy of STIE Mandala students related to potency and community issues, b) Addressing the problems in rural communities targeted by the concept of